KAPASITAS MASYARAKAT DALAM UPAYA PENGURANGAN RESIKO BENCANA BERBASIS KOMUNITAS (PRBBK) DI DESA WONOLELO KECAMATAN PLERET KABUPATEN BANTUL - , FUADGALUHPRIHANANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Activities of Community Based Disaster Risk Reduction (CBDRR) with Community Based Disaster Preparadness (CBDP) method seen as an appropriate method to increase the capacity of communities to manage disaster risks that exist in their area. This study aims to conduct a study on the capacity of the Community Based Disaster Risk Reduction (CBDRR) in the Wonolelo Village, Pleret, Bantul Disctrict. The method used in this research is descriptive quantitative and qualitative, collecting data using using questionnaires and supported by in-depth interviews, observation, document study. The results showed that the level of the community in a capacity to implement the program for Community Based Disaster Risk Reduction (CBDRR) in the village of Wonolelo is high by 68%, the constraints in implementing the CBDR) to the community in the village of Wonolelo include : regulatory and policy aspects of disaster management, cultural aspect, political aspect, and the aspect of education, and strategies to increase community capacity in village level of Wonolelo in disaster risk reduction is to incorporate DRR activity into village RPJM.